A Pair of New Antioxidant Phenolic Acid Stereoisomers Isolated from Danshen Injection (Lyophilized Powder) - Jing Liu; Jianfeng Zhao; Zhong Dai; Ruichao Lin; Gangli Wang; Shuangcheng Ma (Molecules, 2014)
A pair of new phenolic acid stereoisomers, (R)-norsalvianolic acid L (1) and (S)-norsalvianolic acid L (2), was isolated from the Danshen Injection (lyophilized powder). The structural elucidation and stereochemistry determination were achieved by spectroscopic and chemical methods including 1D, 2D NMR (1H-1H COSY, HSQC and HMBC) and circular dichroism experiments. Their antioxidant activities were assessed by the DPPH· and ABTS·+ scavenging methods in vitro with microplate assay. The IC50 values of 1 were 6.9 and 9.7 μM respectively, which was close to the control salvianolic acid B (7.8 and 7.1 μM respectively), while the IC50 values of isomer 2 were 27.1 and 25.3 μM, respectively.